Evaluation of Petunia Cultivars as Bedding Plants for Florida - Richard O. Kelly; Zhanao Deng; Brent K. Harbaugh (EDIS, 2007)
ENH1078, an 11-page illustrated fact sheet by R. O. Kelly, Z. Deng, and B. K. Harbaugh, describes the history of petunia breeding in Florida and summarizes the results of field trials testing best performing cultivars in Florida and comparing the resulting standards with untested varieties from seed companies around the world. Includes a list of high performing cultivars, a table with detailed performance data and digital images of cultivars by class. Published by the UF Department of Environmental Horticulture, October 2007.